Old Theories Revisited on Cancer Assistant Therapy - Lu, Da-Yong; Lu, Ting-Ren; Che, Jin-Yu; Wu, Hong-Ying (International Journal of Medical and Health Sciences Research, 2014)
The causes of cancer deaths are multi-factorials in clinics. Despite the rapid advancement of cancer treatments, many other pathological factors discovered more than half century can also be the targets of cancer therapy. Apart from direct causes from tumor progressions and metastases, many clinical complications or psychiatry factors will more or less speed up these pathogenesis processes of cancer patients, even lost of cancer patients’ life. Based on above-mentioned factors, many types of assistant therapies are designed to counter many harmful clinical complications happening in cancer patients. This mini-review offers the panorama of those therapies, addresses and discusses the history and present advancements. Many key factors and efforts and their future impacts are outlined and highlighted.